2011
DOI: 10.5402/2011/819765
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Dissolution Enhancement of Etoricoxib by Solid Dispersion Technique Using Sugar Carriers

Abstract: The aim of the present study was to improve solubility and dissolution of the poorly aqueous soluble drug, etoricoxib by solvent evaporation technique using various sugar carriers, such as lactose, sucrose, and mannitol. Etoricoxib solid dispersions and their respective physical mixtures using lactose, sucrose, and mannitol were prepared in different ratios by solvent evaporation technique. The percent yield, drug content, saturation solubility, and in vitro dissolution of etoricoxib solid dispersions and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…In the present study, this strategy of forming inclusion complexes of etoricoxib with BCD was investigated for taste masking as well as dissolution enhancement of the drug loaded in MDF. Although many studies have been reported on solubility enhancement and ODT of etoricoxib [4,9] oral thin films of etoricoxib have not been formulated so far and hence our work is first of its kind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, this strategy of forming inclusion complexes of etoricoxib with BCD was investigated for taste masking as well as dissolution enhancement of the drug loaded in MDF. Although many studies have been reported on solubility enhancement and ODT of etoricoxib [4,9] oral thin films of etoricoxib have not been formulated so far and hence our work is first of its kind.…”
Section: Introductionmentioning
confidence: 99%
“…Etoricoxib is practically insoluble in water categorized to BCS class II (low soluble, high permeable). Its poor aqueous solubility and dissolution delay the rate of absorption [4]. Formulation of etoricoxib as MDF would improve its aqueous solubility along with fast dissolution of etoricoxib in mouth itself resulting in earlier drug absorption starting from oral cavity itself leading to rapid pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Etoricoxib, 5-chloro-6 -methyl-3[4-(methyl sulfonyl) phenyl] -2, 3 -bypyridine, is a highly selective second generation cyclooxygenage-2 (COX-II) inhibitor administered orally as an analgesic and nonsteroidal anti-inflammatory drug [14]. It is used in the treatment of rheumatoid arthritis, osteoarthritis, postoperative dental pain, chronic back pain, and acute gout [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] According to the literature, the aqueous solubility of etoricoxib is really low. [5] In this way, the physicochemical information about the solubility of this drug in aqueous and non-aqueous solvent mixtures is not yet complete, although a recent study regarding its solubility in several binary aqueous cosolvent mixtures at 298.2 K has been reported by Rathi et al [6] The authors correlated the variation in the measured equilibrium solubility with binary solvent composition in terms of the Jouyban-Acree model. Etoricoxib was found to exhibit up to a 5200-fold increase in mole fraction solubility in going from water to the organic cosolvents.…”
Section: Introductionmentioning
confidence: 96%